The Association between Ambient Fine Particulate Matter and Oral Neoplasm among Smokers and Betel Quids Chewers - Mei-Sheng Ku; Pallop Siewchaisakul; Amy Ming-Fang Yen; Chen-Yu Liu (Aerosol and Air Quality Research)
Abstract The association between fine particulate matter < 2.5 µm (PM2.5) and oral neoplasm has barely been addressed. The purpose of this study is to elucidate the association between PM2.5 and oral neoplasm, including oral potentially malignant disorder (OPMD) and oral cancer (OC), taking into account the geographical heterogeneity. Data for analysis were derived from nationwide OC screening program, targeting Taiwanese cigarette smokers and/or betel quid chewers, and the Taiwan Air Quality Monitoring Network between 2006 and 2016. Totally 3,864,045 smokers and/or betel quids chewers were enrolled in this study. Among them, 154,030 OPMD cases and 23,286 oral cancers were found during the study period. Information on age, gender, living area, personal oral habits, and monthly PM2.5 concentration in average were collected. We used the Bayesian random-effect logistic regression model to assess the association between PM2.5 and OPMD/OC. After adjusting for sex, age, and behavior of betel quid chewing and cigarette smoking, we found that subjects from areas of higher levels of PM2.5 (≥ 35 µg m−3) had an increased risk of OPMD/OC and OC by 11% (aRR = 1.11; 95% CI: 1.09–1.13) and 55% (aRR = 1.55; 95% CI: 1.49–1.60) respectively, compared to those from areas of lower PM2.5 (< 35 µg m−3). Such effect was further demonstrated in a concentration-dependent manner. Subjects from areas of higher PM2.5 levels were found to have greater risk of OPMD/OC in Taiwan. Future studies are warranted to investigate the effect of personal PM2.5 exposure on OPMD/OC risk.